The Effects of Lock-down 2020 on the Behaviour and Mood of Children Aged Three to Six in Italy - Domiziana Sacchi; Augusto Pasini; Marco Muti; Carla Roverselli; Simonetta Spiridigliozzi (LED Edizioni Universitarie, 2023)
The aim of this research was to trace an association between the lock-down caused by the Covid-19 pandemic in Itlay (March-May 2020) and possible short- and long-term behavioral and mood changes in 1,000 children aged three to six years. With the data collected through the administration of two questionnaires, an account of the psychoattitudinal performance of the subjects examined during the aforementioned period was obtained. The results showed that during the lock-down nearly 60% of the sample exhibited negative feelings; 11.2% of the sample also exhibited symptoms attributable to situational depression. With the return to normalcy, the percentage of negative feelings recorded in the sample decreased to 11%; a significant association was also found between the mood state and temperament of the subjects. Behavioral changes such as increased onychophagy and eating changes during lock-down were recorded, which can be associated with stress. It was possible to reveal problems in the long term, such as difficulty in modulating anxiety, controlling aggression, and social adjustment.